Enhancing ACE-inhibition of food protein hydrolysates by selective adsorption using porous carbon materials. (June 2015) - Hippauf, Felix; Lunow, Diana; Huettner, Christiane; Nickel, Winfried; Borchardt, Lars; Henle, Thomas; Kaskel, Stefan
Abstract: Bioactive peptides from food proteins such as natural ACE (angiotensin-converting enzyme)-inhibitors have attracted particular attention for their potential to prevent hypertension. ACE-inhibiting peptides were enriched from food protein hydrolysates prepared from α-lactalbumin and lysozyme by selective adsorption on microporous activated carbons. For the eluate, it was shown by liquid chromatography that the strongest inhibitor isoleucyl-tryptophan was enriched by a factor of 11.2 compared to the initial α-lactalbumin hydrolysate. Natural inhibitors derived from lysozyme hydrolysates (e.g., alanyl-tryptophan) were successfully enriched as well. Identification of the enriched peptide fraction by mass spectroscopy revealed the hydrophobic character of the enriched peptides. The molecular weight distribution of the enriched peptide fraction can be controlled by the pore size distribution of the chosen adsorbent, which was proven by size exclusion chromatography of enriched peptide fractions derived from three different model carbons differing in their pore size. The selective enrichment of natural ACE-inhibitors from the α-lactalbumin hydrolysate lead to a 6 times stronger in vitro ACE-inhibition demonstrating the high potential as ingredients for hypotensive functional foods with reduced side effects.